Feelings of Inferiority in Adolescents and Implications for Guidance and Counseling Services: A Literature Review - Tjahyani, Annisa Pradita; Saripah, Ipah; Nadhirah, Nadia Aulia (Program Studi Bimbingan Penyuluhan Islam Fakultas Dakwah dan Komunikasi, 2024)
Objective: The study was conducted by the author to investigate inferiority feelings in adolescents and their implications for guidance and counseling.Method: In this research, the author employed a literature review method using various written sources such as books, articles, journals, and documents relevant to the study.Results: The findings indicate that inferiority feelings among adolescents in Indonesia are still relatively high. Inferiority feelings significantly influence individual personality development. Although inferiority feelings can motivate behavior towards superiority, they often lead to maladaptive behavior. Therefore, it is crucial to address these feelings promptly to prevent disruption in adolescent development.Conclusion: Inferiority feelings are a sense of inadequacy or low self-esteem present in every individual, and they are relatively more common during adolescence. Many factors contribute to the emergence of inferiority feelings. Consequently, it is essential to provide treatment through guidance and counseling services. Guidance and counseling serve as educational tools that help shape students' orientation away from the negative ideas instilled by their environment. School counselors are required to assist students in achieving ideal development.Implications: This research is expected to provide information about the dynamics of inferiority feelings in adolescents and serve as a basis for further studies and development.